The role of technology in teaching listening - Shapran, Ludmila; Cherednichenko, Galina; Kunytsia, Lyudmila (My University, 2011)
In the article the authors define the importance of listening in language learning and teaching, they disclose how language teachers can help their students to become effective listeners with the help of technology. In the communicative approach to language teaching, this means modeling listening strategies and providing listening practice in authentic situations: those that learners are likely to encounter when they use the language outside the classroom.
Keywords: аудіювання; language learning; комп'ютерні технології навчання; вивчення іноземної мови; кафедра ділової іноземної мови та міжнародної комунікації